Genealogia femenina en Els jeroglífics i la pedra de Rosetta (1976) de Carmelina Sánchez-Cutillas. - DOMÉNECH, VERÒNICA CANTÓ (Scripta, 2021)
The purpose of this article is to approach female genealogy in the poetry collection Els jeroglífics i la pedra de Rosetta, in order to prove that the presence of certain female figures is not accidental, but rather responds to a clear gender awareness on the part of Carmelina Sánchez-Cutillas. The paper also aims to verify that female typology is opposed to a series of male figures, associated with concepts of authority and oppression, representative of the androcentric patriarchal view of the Francoist society. From the analysis of this book of poems, in which the author incorporates all of her extraordinary cultural background and manifests her erudition, we venture to provide inside into the study of the symbology underlying the fourteen mythological female figures present in the work. They are characterized by features such as universality, strength or wisdom, which are recovered by the writer as voices of the past that return to the present with great evocative force and with a desire to denounce, to rescue us from the silence, the emptiness, the darkness, to regain our consciousness, identity and individual and collective dignity.